Automorphism groups of Cayley digraphs of Z_p^3 - Dobson, Edward; Kovács, István (The Electronic Journal of Combinatorics, 2009)
We calculate the full automorphism group of Cayley digraphs of Z_p^3, p an odd prime, as well as determine the 2-closed subgroups of S_m S_p with the product action.